SOLAS : consolidated edition, 1997 - International Maritime Organization (London : IMO, 1997)
(Consolidated text of the International Convention for the Safety of Life at Sea, 1974, and its Protocol of 1978: articles, annexes and certificates)
Keywords: Maritime safety, Agreements; Safety at Sea, regulations, Agreements